2023
DOI: 10.1002/dc.25190
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic SMARCA4‐deficient undifferentiated tumor with associated granulomatous reaction and response to pembrolizumab

Abstract: Thoracic SMARCA4‐deficient undifferentiated tumor (SMARCA4‐UT) is a rare entity that was recently described in the current World Health Organization Classification of Tumors. These lesions are highly aggressive with dismal prognosis, and most patients present with metastasis at the time of diagnosis. While there are about 100 cases of SMARCA4‐UT described in the literature, there are only few existing reports that describe the cytomorphology of these lesions. We present a patient with masses involving the medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…While one study concerning SMARCA4-deficient NSCLC showed higher chemosensitivity to platinum-based chemotherapy in an adjuvant setting, no study has reported the efficacy of chemotherapy alone in SMARCA4-UT [ 75 ]. In the last few years, many studies have demonstrated the efficacy of immunotherapy in SMARCA4-UT patients both as a monotherapy and in combination with chemotherapy [ 6 , 7 , 8 , 9 , 63 , 76 ].…”
Section: Treatment: Chemotherapy Versus Immunotherapymentioning
confidence: 99%
“…While one study concerning SMARCA4-deficient NSCLC showed higher chemosensitivity to platinum-based chemotherapy in an adjuvant setting, no study has reported the efficacy of chemotherapy alone in SMARCA4-UT [ 75 ]. In the last few years, many studies have demonstrated the efficacy of immunotherapy in SMARCA4-UT patients both as a monotherapy and in combination with chemotherapy [ 6 , 7 , 8 , 9 , 63 , 76 ].…”
Section: Treatment: Chemotherapy Versus Immunotherapymentioning
confidence: 99%
“…Thoracic SMARCA4-deficient undifferentiated tumour (SMARCA4-UT) is an unusual and aggressive tumour. While there are approximately 100 cases of this tumour reported in the literature, 1 there are very few detailed descriptions of its cytomorphologic characteristics (Table 2), and only rare cases in which primary diagnosis was made on cytologic material. Herein we present a case with a detailed description of the appearance on three specimen types: transbronchial needle aspiration (TBNA) cytology, transbronchial needle biopsy (TBNB) and effusion cytology.…”
Section: Introductionmentioning
confidence: 99%